Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal HOTS Ditinjau dari Kemampuan Awal Matematika - Dewi, Amelania; Machromah, Isnaeni Umi (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
Creative thinking capability is one’s ability to solve problems by having several solutions (fluency), using various methods (flexibility), and finding different and unusual solution with correct answer (novelty). Numerous researches have been done about student’s creative thinking capability in solving math problems. However, it is only a small fraction that studies the capability on solving HOTS problems. This research is descriptive-qualitative research, with 6 8th grade class G of SMP Negeri 8 Purwokerto as subjects. The material used in this study is a system of two-variable linear equations. Data are gathered using documentation, test, and interview techniques. To analyze the data, this research used data reduction, presentation, and conclusion, while also using triangulation methods. The result of this research shows that: 1) Students with high competency in basic math meet the level of HOTS and achieved all three indicators of creative thinking fluency, flexibility, and novelty; 2) Students with moderate competency meet the level of HOTS and achieved two indicators which are fluency and flexibility; 3) Students with low competency in basic math meet the level of HOTSand could only achieve one out of three indicators of creative thinking that is fluency.